Land degradation in Mediterranean Europe: can agroforestry be a part of the solution? A prospective review - Houérou, H N (Agroforestry Systems, 1993)
Vegetation and land degradation, although less acute than in the Southern Medi- terranean Basin, is still widespread in the North. Degradation results from various kinds of mismanagement of the land. Wildfires, for instance, favoured by ungrazing, play an increas- ingly important role as the mean area annually burnt shifted from an average 200,000 ha in the 1960's to over 600,000 ha in the 1980's. These put a heavy burden on the states and on local communities that amounted to an annual average one billion ECUs (USS 1.2 billion) in the 1980's. The causes and processes of land and vegetation degradation are analysed in the light of the changes in land-use over the past 25 years, as shown in the official statistical data. Forest and shrubland areas are expanding while farmland is shrinking by nearly 1% per annum. An analysis of the foreseeable situation in the early years of the twenty-first century is attempted on the basis of the likely evolution of the EEC agricultural policy. Some guidelines are proposed for sound ecological management of the Northern Mediterranean land and vegeta- tion. These include the introduction or expansion of agroforestry systems with multiple-use of the land to develop tourism, wildlife, hunting and sports, combined with extensive grazing of livestock and game and timber production from elite clones of selected high yielding or highly valued species. Eight to ten million hectares, at present devoted to cereal cropping (i.e. about 50% of the cereal-cropping hectarage), will have to be reconverted to other activities. By 1995, the EEC cereal prices will have to drop in line with the world market, as a result of the recent evolution of the EEC Communal Agricultural Policy (CAP). The warranted EEC cereal prices are at present about 40% above that of the world market. The reconversion of this cereal land to other activities could combine low-input mixed agroforestry systems with extensive livestock and game husbandry, high value timber, tourism and various amenities. These should include forage-shrubs plantations in a strategy which combines inexpensive, albeit nutritionally balanced, ruminant diets with erosion control and the overall uplift of natural land fertility and productivity.
Keywords: agroforestry systems; fodder shrubs; Mediterranean basin; multipurpose production systems; range management; sylvo-pastoralism